Simple Screening Tests for the Detection of Metallo-β-Lactamase (MBL) Production in Clinical Isolates of Pseudomonas and Acinetobacter - Anwar, Shaheda; Miah, Md Ruhul Amin; Saleh, Ahmed Abu; Sattar, Humayun; Ahmed, Sharmeen (Ibrahim Medical College Journal, 2010)
There are no standard methods for the detection of metallo-β-lactamase (MBL) production in gram negative organism in routine microbiology practice. The present study was undertaken to evaluate the screening tests like double disk synergy test (DDST) and disk potentiation test (DPT) using ceftazidime (CAZ) and imipenem (IPM) disks with chelating agents like EDTA, 2-mercaptopropionic acid (2-MPA). A total of 132 Pseudomonas and 76 Acinetobacter isolates were obtained from Bangabandhu Sheikh Mujib Medical University (BSMMU) and Bangladesh Institute of Research and Rehabilitation for Diabetes, Endocrine and Metabolic Disorders (BIRDEM) hospitals of Dhaka city. A total of 53 and 29 IPM resistant Pseudomonas and Acinetobacter isolates were selected. EDTA-IPM microdilution minimum inhibitory concentration (EDTA-IPM MIC) method detected MBL in 44 (83%) IPM resistant Pseudomonas and 19 (65.5%) Acinetobacter isolates. DDST with CAZ-0.1M EDTA and CAZ-2-MPA detected MBL in 73.6% and 67.9% of IPM resistant Pseudomonas and 55.2% and 48.3% of Acinetobacter isolates respectively. The detection rate was 67.9% and 66.1% in Pseudomonas and 51.7% and 44.8% in Acinetobacter isolates by EDTA-IPM and IPM-2- MPA methods respectively. In comparison to DDST, DPT with CAZ-0.1M EDTA showed higher sensitivity (89.7% ) and specificity (100%) for detection of MBL in Pseudomonas and Acinetobacter. The results showed that simple screening tests like DPT with 0.1M EDTA was able to detect MBL producing Pseudomonas and Acinetobacter from clinical samples with high sensitivity and specificity. Ibrahim Med. Coll. J. 2010; 4(1): 26-30 DOI: 10.3329/imcj.v4i1.5932